Differences in Common Genetic Predisposition to Ischemic Stroke by Age and Sex. Issue 11 (November 2015) - Traylor, Matthew; Rutten-Jacobs, Loes C.A.; Holliday, Elizabeth G.; Malik, Rainer; Sudlow, Cathie; Rothwell, Peter M.; Maguire, Jane M.; Koblar, Simon A.; Bevan, Steve; Boncoraglio, Giorgio; Dichgans, Martin; Levi, Chris; et al.
Abstract : Background and Purpose—: Evidence from epidemiological studies points to differences in factors predisposing to stroke by age and sex. Whether these arise because of different genetic influences remained untested. Here, we use data from 4 genome-wide association data sets to study the relationship between genetic influence on stroke with both age and sex. Methods—: Using genomic-relatedness-matrix restricted maximum likelihood methods, we performed 4 analyses: (1) we calculated the genetic correlation between groups divided by age and (2) by sex, (3) we calculated the heritability of age-at-stroke-onset, and (4) we evaluated the evidence that heritability of stroke is greater in women than in men. Results—: We found that genetic factors influence age at stroke onset ( h 2 [SE]=18.0 [6.8]; P =0.0038), with a trend toward a stronger influence in women (women: h 2 [SE]=21.6 [3.5]; Men: h 2 [SE]=13.9 [2.8]). Although a moderate proportion of genetic factors was shared between sexes ( rG [SE]=0.68 [0.16]) and between younger and older cases ( rG [SE]=0.70 [0.17]), there was evidence to suggest that there are genetic susceptibility factors that are specific to sex ( P =0.037) and to younger or older groups ( P =0.056), particularly for women ( P =0.0068). Finally, we found a trend toward higher heritability of stroke in women although this was not significantly greater than in men ( P =0.084). Conclusions—: Our results indicate that there are genetic factors that are either unique to or have a different effect between younger and older age groups and between women and men. Performing large, well-powered genome-wide association study analyses in these groups is likely to uncover further associations. Abstract : Supplemental Digital Content is available in the text.